The Implementation of Collaborative Activities between Forest Farmer Groups (KTH) and Gularaya Forest Management Unit (KPH) in Community Forest in Ambololi Village , Konda Sub district, South Konawe Regency - Hafidah Nur; Satya Agustina Laksananny; La Ode Agus Salim Mando; Sitti Marwah; waode maratun shaliha (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2024)
This study aims to examine the factors that influence and types of collaboration between Forest Farmer Groups (KTH) and Forest Management Units (KPH) Gularaya in community forests in Ambololi Village, Konda District, South Konawe Regency.Community involvement in forest management is very important to improve the sustainability of productivity and welfare of local communities. This study uses aqualitative descriptive method with primary data obtained through observation, interviews, and questionnaires from 30 KTH members. The results of the study indicate that the factors that influence collaboration between KTH and KPH consist of internal factors such as knowledge, education, farming experience, and number of family dependents, as well as external factors such as extension activities, culture, and access to information, play an important role in the collaboration. The types of collaboration found include planning, decision making, activity implementation, technical and financial support, access to facilities, and marketing of forest products. This collaboration is important to maximize the sustainable use of forest resources by combining local knowledge and technical expertise from KPH Gularaya.